Oxygen Saturation Sebagai Prediktor Mortality Klien Cedera Kepala Yang Lebih Baik Dari Respiratory Rate - Ristanto, Riki; Zakaria, Amin (Universitas Tribhuwana Tunggadewi, 2019)
The Revised Trauma Score (RTS) is a predictor of moderate mortality in head injury clients. To increase it by changing the respiratory rate (RR) component in RTS with other respiration components that have the potential to have a higher correlation to the mortality of head injury clients. The aim of this study was to analyze differences in RR accuracy and oxygen saturation (SpO2) as predictors of mortality in head injury clients. This study is an observational analytic study with a cohort retrospective study approach, conducted at the hospital. Dr. Iskak Tulungagung. The population is a head injury client medical record for the period January to December 2017, with a purposive sampling technique which obtained a sample of 150 respondents. Data analysis using the Mann-Whitney test, logistic regression, and ROC Curve comparison. The results, the variables RR and SpO2 have a significant relationship with the mortality of head injury clients(p value = 0.000). Logistic regression test results, RR equation has sensitivity = 0.792 (79.2%), specificity= 0.7333 (73.33%), Positive Predictive Value (PPV) = 0.922 (92.2%), and Negative Predictive Value (NPV) = 0.468 (46.8 %). The SpO2 equation has sensitivity = 0.907 (90.7%), specificity = 0.881 (88.1%), PPV= 0.951 (95.1%), and NPV = 0.787 (78.7%). The results of a comparison analysis of the ROC curve, concluded that ROC SpO2 (AUC = 0.930) was better than ROC RR (AUC = 0.729). Oxygen saturation is a better predictor of mortality of head injury clients than RR.